(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
The expansion of the railway industry in Malaysia has brought about numerous benefits, including improved transportation and reduced traffic congestion. However, the increased presence of railway systems has also resulted in the issue of noise pollution caused by moving trains, negatively impacting the well-being of nearby residents. This study aims to explore the correlation between permitted noise limits and actual noise levels produced by trains near residential areas in Malaysia. The findings indicate that the measured noise levels exceeded the allowable limits set by the Department of Environment (DOE) guidelines. Additionally, the study revealed significant correlations between various variables and the magnitude of noise emissions generated by moving trains. These findings highlight the need for effective noise mitigation strategies and further research to address the concerns of residents living near railway tracks. The results contribute to a better understanding of the impact of railway noise on communities and provide valuable insights for future noise management initiatives in the Malaysian railway industry.